Terrestrial habitats in Changxing Chinese Alligator Nature Reserve of Zhejiang and their effects on the egg laying of the female alligators - WANG Zhenwei; LIN Jianqing; ZHONG Guoheng; SUN Li; FANG Shengguo (浙江大学学报. 农业与生命科学版, 2021)
In this research, we surveyed the habitat factors in different regions in the core area of Changxing Chinese Alligator (Alligator sinensis) Nature Reserve of Zhejiang Province and their effects on the egg laying of the female alligators during the breeding season. The results revealed that the female alligators preferred to build nests on the regions covered with dense bamboo groves or tall trees. Few nests were found on the regions dominated by weeds and with few tall dominant trees. Investigation on the habitat factors in different regions showed that the dry mass of litter per unit surface area, the height of dominant species and the surface slope were the three major factors that affected the female alligators to choose the site for nesting. The above results could provide references for the habitat optimal transformation, and for the novel habitat selection. Our results could also facilitate the development of conservation programs for Chinese alligator.